The Context of the Collaborative Governance Systems in Organic Waste Management is a Public Service in the Urban Area of Lebak Regency - Wicaksana, Harits Hijrah; Parmanto, Chandra; Fauzi, Muhammad (Universitas Padjadjaran, 2025)
Organic waste management in urban areas of Lebak Regency has become an unresolved polemic reaching 62.28% of unmanaged waste in 2017-2022, dominated by food waste at 30%. Collaborative governance is a strategic approach to improving the effectiveness of public services in this field. Through active involvement across public, private, and civil sectors at every stage of waste management. This study aims to analyze the collaborative governance model applied, identify factors, and provide strategic recommendations using descriptive qualitative methodology to describe organic waste management in a complete and in-depth manner. The findings indicate a lack of optimization of public and civil sector collaboration such as public awareness and participation in sorting and collecting organic waste from inorganic in households. Likewise, collaboration with the private sector has not been optimized into long-term cooperation. The lack of public sector roles such as commitment, capacity, and effective coordination mechanisms, needs to be strengthened through continuous outreach and socialization activities, or collaborating with the Education Office to provide education on organic waste management in schools. In addition, the formation of an organic waste management forum by the Environmental Service and act as a network broker as a liaison across sectors engaged in organic waste management.